Kendala Guru SMPN 2 Dompu dalam Desain Modul dan Asesmen Projek Penguatan Profil Pelajar Pancasila (P5) Kurikulum Merdeka - Arif Bulan; Hasan; Nurjanah; Ilyas; Sandi Ahmad Pratama (PT. Banjarese Pacific Indonesia, 2024)
Research on the constraints of teachers at SMPN 2 Dompu in module design and assessment of the project to strengthen the profile of Pancasila students (P5) in the Independent Curriculum is very important to carry out because one of the important aspects of the independent curriculum is P5. This research aims to find out what obstacles the teachers of SMPN 2 Dompu have in designing modules and assessing the project to strengthen the Pancasila student profile (P5) of the Merdeka Curriculum. The research method used in this research is a qualitative method. The data analysis technique used in this research is a data analysis technique developed by Creswell including data collection, data reduction, data display, and drawing conclusions. The results of this research are that there are 6 teacher obstacles. The first teacher has difficulty identifying the readiness stages of educational units in designing modules and project assessments to strengthen the profile of Pancasila students (P5). Second, teachers have difficulty determining dimensions and themes in designing modules and assessments for projects to strengthen the profile of Pancasila students (P5). Third, teachers have difficulty designing and determining time allocation in module design and assessment as well as implementing projects to strengthen the profile of Pancasila students (P5). Fourth, teachers have difficulty developing topics and activity lines in designing modules and assessments for projects strengthening the profile of Pancasila students (P5). Fifth, teachers have difficulty creating and designing project modules for strengthening Pancasila student profiles (P5). Sixth, teachers do not yet understand how to create assessment and assessment rubrics in the project to strengthen the profile of Pancasila students (P5). Recommendations from the results of this research are (1) the Dompu Regency Youth and Sports Education Office must provide training related to P5 module design and P5 Assessment to teachers at SMPN 2 Dompu, (2) Principals must collaborate with campus or external parties to conduct training for teachers.